1998
DOI: 10.1097/00006982-199806000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Piperacillin Into the Vitreous After Intravenous Administration

Abstract: Studies show that intravenously administered piperacillin can penetrate the vitreous cavity in rabbits. Our study suggests that a single dose of piperacillin can produce intravitreal concentrations sufficient to kill gram-positive bacteria in inflamed eyes. The poor intraocular penetration of systemically administered piperacillin in uninflamed eyes raises questions about its usefulness as a prophylactic agent in ophthalmic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our study found elevated levels of penicillin in the intravitreal space of an inflamed eye following intravenous administration, as seen with piperacillin [10]. This correlates well with studies that have found increased penetration of systemic antibiotics in inflamed eyes versus their non-inflamed counterparts [10,15]. In inflamed eyes, drugs cleared by the posterior route, such as betalactams, demonstrate delayed clearance due to compromise of the RPE pump [15].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study found elevated levels of penicillin in the intravitreal space of an inflamed eye following intravenous administration, as seen with piperacillin [10]. This correlates well with studies that have found increased penetration of systemic antibiotics in inflamed eyes versus their non-inflamed counterparts [10,15]. In inflamed eyes, drugs cleared by the posterior route, such as betalactams, demonstrate delayed clearance due to compromise of the RPE pump [15].…”
Section: Discussionsupporting
confidence: 89%
“…Anionic drugs including beta-lactams are subject to accelerated clearance via active transport across the BRB which, in this case, may have further promoted diffusion from the plasma into the vitreous cavity following the concentration gradient [15]. Our study found elevated levels of penicillin in the intravitreal space of an inflamed eye following intravenous administration, as seen with piperacillin [10]. This correlates well with studies that have found increased penetration of systemic antibiotics in inflamed eyes versus their non-inflamed counterparts [10,15].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Alfaro et al [27] studied the effect of traumatism on the ocular penetration of intravenous ciprofl oxacin in rabbits and pigs, and found that the drug levels increased by three or four times compared with control eyes. In another study, Robinet et al [28] found that drugs which usually do not achieve detectable levels in the human eye, such as piperacillin, could be detected under infl ammatory states. Our study shows that infl ammation leads to a better drug penetration.…”
Section: Infl Ammation Induced By Endotoxin and Changes In Antibioticmentioning
confidence: 99%
“…Intravitreal antibiotic applications represent a superior means and route for the treatment of endophthalmitis, as the intraocular penetration of systemic antibiotics is poor [2][3][4]. Although vancomycin and aminoglycosides are the two most commonly used antibiotics at present, there has been increasing evidence of resistance to these agents [5].…”
Section: Introductionmentioning
confidence: 99%